2023
DOI: 10.3389/fimmu.2023.1125876
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD8+CD28+ T lymphocytes predict the efficacy and safety of PD-1/PD-L1 inhibitors in cancer patients

Abstract: BackgroundProgrammed cell death protein-1/programmed cell death ligand-1 (PD-1/PD-L1) inhibitors works by reactivating immune cells. Considering the accessibility of noninvasive liquid biopsies, it is advisable to employ peripheral blood lymphocyte subsets to predict immunotherapy outcomes.MethodsWe retrospectively enrolled 87 patients with available baseline circulating lymphocyte subset data who received first-line PD-1/PD-L1 inhibitors at Peking Union Medical College Hospital between May 2018 and April 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Moreover, numerous studies have indicated that immune cell phenotypes can serve as central biomarkers for immunotherapy. [ 49 , 59 , 68 70 ] Therefore, the 15 negative immune phenotypes we analyzed in our research may be essential biomarkers supporting immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have indicated that immune cell phenotypes can serve as central biomarkers for immunotherapy. [ 49 , 59 , 68 70 ] Therefore, the 15 negative immune phenotypes we analyzed in our research may be essential biomarkers supporting immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of circulating CD8 + CD28 + T cells are a potential biomarker for immunotherapy response and better prognosis. 31 CD28 is involved as the receptor for the second signal of T-cell activation and is a marker for an effector memory population of T cells following adoptive transfer. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Tem cells have been extensively studied as predictive markers of the baseline response to anti-PD-(L)1 therapy in patients with NSCLC ( 14 , 15 ). Recent studies have demonstrated that anti-PD-(L)1 therapy does not reverse the phenotype of terminally exhausted T cells but promotes the differentiation of self-renewing progenitor T cells into newly formed effector-like T cells, including memory T cells ( 37 ).…”
Section: Cd8 + T Cell Subsets As a Potential Bioma...mentioning
confidence: 99%
“…Using 190/μL as the cut-off, patients with higher CD8 + CD28 + T cell counts exhibited significantly prolonged median PFS than patients with lower counts (not reached vs. 8.7 months, p < 0.001). In addition, they had a significantly extended overall survival (OS) (not reached vs. 16.2 months, p < 0.001) ( 15 ). These findings suggest that Tem cells are strongly associated with response to PD(L)1 therapy.…”
Section: Cd8 + T Cell Subsets As a Potential Bioma...mentioning
confidence: 99%
See 1 more Smart Citation